Auditory Mismatch Negativity in Youth Affected by Autism Spectrum Disorder With and Without Attenuated Psychosis Syndrome - Di Lorenzo, Giorgio; Riccioni, Assia; Ribolsi, Michele; Siracusano, Martina; Curatolo, Paolo; Mazzone, Luigi (Frontiers in Psychiatry, 2020)
The present study investigates differences in the auditory mismatch negativity (MMN) parameters given in a sample of young subjects with Autism Spectrum Disorder (ASD, n:37) with or without co-occurent Attenuated Psychosis Syndrome (APS). Our results show that ASD individuals present an MMN decreased amplitude and prolonged latency, without being influenced by concurrent APS. Additionally, when correlating the MMN indexes to clinical features, in the ASD+APS group we found a negative correlation between the severity of autistic symptoms and the MMN latency in both, frequency (f-MMN r=-.8106; p<.0001) and duration (d-MMN r=-.6504; p=.006) deviants. Thus, our results may provide a more informative characterization of the ASD sub-phenotype when associated to APS, highlighting the need of further longitudinal investigations.